Social media as a platform for resistance: examining the language of dissent in Indian society - Ashwini, D. Y.; Vishwanatha,; Puneeth, R. P. (Frontiers in Communication, 2025)
IntroductionSocial media plays a crucial role in present-day resistance movements by amplifying marginalized voices, fostering global solidarity, and challenging hegemonic narratives. Despite its impact, research on algorithmic biases, multimodal communication tools (like memes and hashtags), and linguistic strategies in digital activism remains limited.MethodsThis study investigates how activists use digital tools and language to engage audiences and navigate platform restrictions. Using a mixed-methods approach, the research analyses 5,000 posts from Twitter, Facebook, and Instagram, selected through stratified sampling for diverse representation. The dataset was refined with Natural Language Processing tools and supported by discourse and sentiment analysis. In-depth interviews with activists were also conducted.ResultsFindings show that activists frequently employ code-switching, viral hashtags, and visual content—especially on Twitter, which proves most effective for political causes. However, algorithmic filtering reduces the visibility of politically sensitive content, and linguistic variations emerge across regions due to local influences.DiscussionMost posts convey neutral or negative sentiments, highlighting the urgency and emotional weight of resistance efforts. These insights emphasize the need for improved content moderation, algorithmic transparency, and equitable digital access for underrepresented communities.